Combining exercise and nanoparticle-based therapies: a review of physiological synergies and pharmacological potential - Wang, Qinhai; Sun, Jinxiang; Su, Zhanguo; Xiang, Lijuan (Frontiers in Pharmacology, 2026)
The convergence of nanotechnology and exercise science represents a novel pharmacological approach to enhance therapeutic efficacy, physiological resilience, and performance outcomes. Exercise is known to induce systemic adaptations—such as improved mitochondrial biogenesis, enhanced antioxidant defense, and neuroplasticity—while nanoparticles offer advanced pharmacokinetic profiles, including targeted delivery, controlled release, and increased bioavailability. Recent preclinical studies suggest that combining nanoparticle-based interventions with structured physical activity may produce synergistic effects that surpass the benefits of either strategy alone. This review critically examines the underlying molecular and cellular mechanisms involved in these interactions, with a focus on oxidative stress modulation, mitochondrial function, and neuroprotective pathways. Evidence from animal models highlights improvements in endurance, muscle regeneration, and cognitive preservation when bioactive compounds (e.g., resveratrol, curcumin, iron) are delivered via nanoparticle formulations. Notably, nano-encapsulation enhances pharmacodynamic outcomes compared to conventional delivery systems. Despite these promising findings, clinical translation remains limited, underscoring the urgent need for human trials to determine safety, optimal dosing, and sex-specific responses. Emerging directions include the integration of wearable biosensors for real-time monitoring, personalized exercise-nanotherapy protocols, and applications in neurodegenerative and metabolic disorders. Bridging nanomedicine and exercise pharmacology may unlock new pathways for precision health interventions.